The Effect of Supplementary Feeding on Stunting Toddlers: Literature Review - Ramdani, Hasbi Taobah; Murtiningsih, Murtiningsih (Karsa Husada Health Institute Garut, 2024)
Stunting, a condition of impaired growth in toddlers due to chronic malnutrition, remains a global health issue, particularly in developing countries like Indonesia. Factors such as poor nutrition, frequent infections, and inadequate healthcare contribute to its prevalence. Supplemental feeding, especially with foods rich in calories, protein, and micronutrients, is a proven approach to improving the nutritional status of stunted children. This study reviews literature from 2015 to 2024, utilizing databases like ScienceDirect, PubMed, Springer, Sagepub, and Google Scholar, with keywords including